Negative electrode active material for improving battery cycle life and preparation method, zinc-nickel battery negative electrode material and negative electrode
By using sulfur-doped carbon to coat calcium zincate crystals in the negative electrode material of zinc nickel batteries, the problem of short cycle life of zinc nickel batteries is solved, and higher battery cycle life and charge and discharge efficiency are achieved.
Patent Information
- Application Number
- CN202210853769.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-07-12
AI Technical Summary
The cycle life of zinc-nickel batteries is relatively short, mainly due to the selection of positive and negative electrode materials, the electrode active surface area decreases and capacity decreases, which in turn affects the cycle performance of the battery.
The sulfur-doped carbon-coated calcium zincate crystal is used as the negative electrode active material, and is prepared by ball milling and spray drying to form a uniform carbon coating layer to improve the conductivity and cyclic stability of the electrode.
Effectively inhibit the growth of zinc dendrites, reduce the concentration of zincate in the electrolyte, and improve the cycle life and charge and discharge efficiency of the battery.
Smart Images

Figure CN115241429B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode active material for improving the cycle life of a battery and a preparation method thereof, a negative electrode material and a negative electrode of a zinc-nickel battery. Background Art
[0002] Zinc-nickel batteries have the advantages of high safety, no combustion and explosion, environmental protection and economy, and high mass-to-energy ratio, making them one of the more popular batteries in the current new energy industry. Compared with existing secondary alkaline batteries, the mass-to-energy density of zinc-nickel batteries can reach 80-120Wh / kg, which is much higher than lead-acid batteries and cadmium-nickel batteries. In addition, zinc-nickel batteries are non-toxic and pollution-free, which has great advantages over existing nickel-cadmium batteries; and compared with existing lithium-ion batteries, they are highly safe, non-combustible and non-explosive, and can be used in fields with higher safety requirements. In addition, zinc, as the main material of the battery's negative electrode, is inexpensive, which reduces the manufacturing cost of the battery. Finally, zinc-nickel batteries have excellent high-rate performance, can be charged and discharged with large currents, and have good low-temperature performance, making them one of the most promising batteries in the field of power batteries.
[0003] However, the service life of zinc-nickel batteries is short, which has become a major problem that has long restricted the development of zinc-nickel batteries. The reasons for the short service life of zinc-nickel batteries include defects in positive and negative electrode materials, electrolytes, diaphragms, battery structure, assembly process, etc. The key factor lies in the selection of positive and negative electrode materials.
[0004] In response to this technical difficulty, the prior art attempts to add additives such as metals, metal oxides or metal hydroxides to the zinc negative electrode, among which calcium hydroxide is a more studied additive. It forms a low-solubility calcium zincate compound with the discharge product zinc oxide of the zinc electrode to reduce the solubility of the zinc compound in the electrolyte, reduce the deformation of the zinc electrode, and thus improve the electrochemical performance of the zinc electrode. However, since irregular calcium zincate is prone to uneven zinc deposition during charging, the shape will change after multiple charges and discharges, the electrode will become thinner around and thicker in the middle, the active surface area of the electrode will decrease, and the electrode capacity will decrease, resulting in a significant shortening of the cycle life of the zinc-nickel battery. The improvement of the life of the zinc-nickel battery is still very limited; and the calcium zincate material prepared by the existing method usually exhibits a lower capacity, and the rate performance needs to be improved. Summary of the invention
[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is how to improve the cycle life of zinc-nickel batteries.
[0006] In order to solve the above technical problems, the first aspect of the present invention provides a negative electrode active material for improving the cycle life of a battery, wherein the negative electrode active material is sulfur-doped carbon-coated calcium zincate crystals, and the raw materials of the sulfur-doped carbon-coated calcium zincate crystals include zinc oxide, hydrophilic calcium hydroxide, a carbon source, a sulfur-containing compound and deionized water.
[0007] Furthermore, the raw material mass ratio of the sulfur-doped carbon-coated calcium zincate crystal is zinc oxide: hydrophilic calcium hydroxide: carbon source: sulfur-containing compound: deionized water = 1: (0.01-0.5): (0.1-0.5): (0.01-0.5): (0.5-2). The mass ratio of each material is within this ratio range to ensure that calcium zincate crystals can be generated and a sulfur-doped carbon coating layer is formed on the surface of the calcium zincate crystal.
[0008] Furthermore, the carbon source is selected from one or more of the following: glucose, sucrose, fructose and starch. The carbon source is an aldehyde compound that is easily soluble in water, provides carbon elements, and forms a carbon coating structure on the surface of the calcium zincate crystal.
[0009] Further, the sulfur-containing compound material is selected from one or more of the following: thiourea, L-cysteine, L-histidine, thioacetic acid and methionine. The sulfur-containing compound is a soluble sulfide that can be effectively dispersed in an aqueous solution, and the sulfur-containing compound is used to provide the sulfur element required for doping.
[0010] Furthermore, the particle size of the hydrophilic calcium hydroxide is 50-200 nm. The particle size of the hydrophilic calcium hydroxide is limited so that the hydrophilic calcium hydroxide of this particle size can be effectively miscible with zinc oxide during the preparation of the precursor, thereby increasing the stability of the precursor.
[0011] The second aspect of the present invention provides a method for preparing the above-mentioned negative electrode active material for improving the cycle life of a battery, comprising the following steps:
[0012] S1. Add grinding media to a ball mill, weigh zinc oxide, hydrophilic calcium hydroxide and deionized water, add them to the ball mill and mix them to form a precursor slurry; the reaction formula of zinc oxide and calcium hydroxide in an alkaline solution is as follows: Ca(OH)2+2Zn(OH)2+2H2O→Ca(OH)2·2Zn(OH)2·2H2O;
[0013] S2, weighing a carbon source and a sulfur-containing compound, adding them to the precursor slurry, and continuing ball milling to form a mixed slurry;
[0014] S3, placing the mixed slurry into a spray dryer for spray drying to obtain a dry raw material powder;
[0015] S4, placing the raw material powder in a calcining furnace, heating it to a set temperature under the protection of an inert gas, calcining it at the temperature, and cooling it to room temperature to obtain sulfur-doped carbon-coated calcium zincate crystals.
[0016] Furthermore, in step S4, the calcination temperature is 700-1000° C., and the holding time is 2-6 hours.
[0017] Furthermore, the grinding media in step S1 includes five sizes of zirconia balls, and the mass ratio of the zirconia balls of each size is 10 mm diameter zirconia ball: 5 mm diameter zirconia ball: 2 mm diameter zirconia ball: 1 mm diameter zirconia ball: 0.5 mm diameter zirconia ball = 1: (1-2): (1-3): (4-7): (5-10). Zirconia balls have the advantages of high strength, high toughness, good wear resistance, high temperature resistance, and corrosion resistance, and have little dispersion and pollution to the ground material. Mixing the zirconia balls according to a certain diameter and weight ratio can control the particle size of the material within the required range.
[0018] Furthermore, in step S1 and step S2, the rotation speed of the ball mill is 5-50 rad / min, and the ball milling time is 15-60 min. The raw materials are processed in the ball mill, which not only allows the materials to be fully mixed, facilitates the adjustment of the material viscosity to make it more suitable for the feed processing of the spray dryer, but also the materials after ball milling have high uniformity, more uniform particle size, and larger specific surface area, so that the sulfur-doped carbon coating layer can be more evenly covered on the surface of the calcium zincate crystal particles during the spray drying process.
[0019] Furthermore, in step S3, the feed temperature of the slurry entering the spray dryer is 160-300°C, the discharge temperature is 60-160°C, the feed rate is 1-5L / h, and the centrifugal disk speed of the spray dryer is 3000-5000rad / min. The spray dryer can complete drying and granulation at the same time, and the surface area of the feed liquid is greatly increased after atomization. By controlling the feed temperature, discharge temperature and feed rate of the slurry entering the spray dryer, a raw material powder with uniform particle size, good fluidity, good solubility, high product purity and good quality can be obtained.
[0020] The third aspect of the present invention provides a zinc-nickel battery negative electrode material, which includes the above-mentioned negative electrode active material for improving the battery cycle life.
[0021] A fourth aspect of the present invention provides a zinc-nickel battery negative electrode, comprising a current collector and the negative electrode material described above, wherein the negative electrode material is coated on the current collector.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention modifies the zinc electrode material, and the negative electrode active material used is sulfur-doped carbon-coated calcium zincate crystals, which have much lower solubility in alkaline electrolyte than zinc oxide, thereby reducing the zincate Zn(OH)4 2- The concentration in the electrolyte can effectively inhibit the dendrite growth of the zinc negative electrode during the battery charging process, thereby effectively improving the performance of the zinc-nickel battery and extending the cycle life of the zinc-nickel battery.
[0024] (2) The sulfur and carbon in the negative electrode active material of the present invention both have the ability to adsorb zinc, which can inhibit the dissolution of zincate ions; sulfur-doped carbon can effectively improve the electrolyte wettability of carbon-coated calcium zincate crystals, which is beneficial to improving the hydroxide ion conduction in the electrode, and is helpful for high-current charging and discharging of zinc-nickel batteries; the doped sulfur can also coordinate with sulfur-philic elements such as Sn, Sb, and Bi in the electrolyte to form metal coordination polymers, optimize the composition, structure and thickness of the carbon coating layer, increase the specific capacity of the electrode material, increase the hydrogen escape potential of the electrode material, and further improve the charging and discharging efficiency.
[0025] (3) The preparation method of the negative electrode active material of the present invention adopts a ball mill to ball mill the raw materials so that the raw materials can be fully mixed. The viscosity of the material can be adjusted by controlling the speed and time of the ball mill, so that it is more suitable for the feed processing of the spray dryer. In addition, five zirconium oxide balls of different sizes are added to the ball mill as grinding media. After ball milling, the material has high uniformity, more uniform particle size and larger specific surface area. During spray drying, zinc oxide and calcium zincate are rapidly generated into calcium zincate crystals, and with the centrifugal atomization of spray drying, the particles are smaller and the specific surface area is larger. The formed calcium zincate crystal particles have high uniformity and are coated with a layer of sulfur-doped carbon on the outside. After high-temperature sintering, a conductive carbon layer is formed on the outside, which increases the conductivity of calcium zincate. The calcium zincate crystals formed in the early stage can remain intact after high-temperature sintering. After being used as electrode active substances, they combine with water in the electrolyte to form a stable calcium zincate compound again. This material not only improves the conductivity of the electrode, but also the formation of calcium zincate is beneficial to improving the dissolution of the zinc negative electrode and increasing the cycle life of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A flow chart of a process for preparing a negative electrode active material provided in an embodiment of the present invention;
[0027] Figure 2 Scanning electron microscope image of the negative electrode active material prepared in Example 1 of the present invention Figure 1 ;
[0028] Figure 3 Scanning electron microscope image of the negative electrode active material prepared in Example 1 of the present invention Figure 2 ;
[0029] Figure 4This is a scanning electron microscope image of calcium zincate crystals. DETAILED DESCRIPTION
[0030] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0031] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0032] A specific embodiment of the present invention provides a zinc-nickel battery negative electrode, which includes a current collector and a negative electrode material coated on the current collector. The negative electrode material includes a negative electrode active material that improves the battery cycle life, and the negative electrode material may also include additives, conductive agents, binders, dispersants, etc. The negative electrode active material is sulfur-doped carbon-coated calcium zincate crystals, which are prepared by reacting zinc oxide, hydrophilic calcium hydroxide, a carbon source, a sulfur-containing compound and deionized water.
[0033] In a specific embodiment, the mass ratio of raw materials of the negative electrode active material is zinc oxide: hydrophilic calcium hydroxide: carbon source: sulfur-containing compound: deionized water = 1: (0.01-0.5): (0.1-0.5): (0.01-0.5): (0.5-2).
[0034] Among them, the carbon source is an aldehyde compound that is easily soluble in water, such as glucose, sucrose, fructose, starch, etc.; the sulfur-containing compound is thiourea, L-cysteine, L-histidine, thioacetic acid, methionine, etc. that are easily soluble in water. Preferably, the particle size of the hydrophilic calcium hydroxide is 50-200nm.
[0035] The preparation method of the above negative electrode active material is as follows Figure 1 As shown, the following steps are included:
[0036] S1. Add grinding media to a ball mill, weigh zinc oxide, hydrophilic calcium hydroxide and deionized water, add them to the ball mill and mix them to form a precursor slurry. The reaction formula of zinc oxide and calcium hydroxide in alkaline solution is as follows: Ca(OH)2+2Zn(OH)2+2H2O→Ca(OH)2·2Zn(OH)2·2H2O. Zinc oxide and calcium hydroxide react chemically in alkaline solution to form calcium zincate, which is insoluble in alkali. The solubility of calcium zincate in alkaline electrolyte is much lower than that of zinc oxide, thereby reducing the concentration of zincate in the electrolyte. During the charging process of the battery, the dendrite growth of the zinc negative electrode is effectively inhibited, which can effectively improve the performance of zinc-nickel batteries and thus extend the cycle life of zinc-nickel batteries.
[0037] S2, weighing a carbon source and a sulfur-containing compound, adding them to the precursor slurry obtained in step S1, and continuing ball milling to form a mixed slurry. The carbon source and the sulfur-containing compound are prepolymerized in water to obtain a water-soluble prepolymer.
[0038] In steps S1 and S2, the speed of the ball mill is 5-50 rad / min, and the ball milling time is 15-60 min. The viscosity of the slurry can be regulated by controlling the speed and time of the ball mill to make it more suitable for the feed processing of the spray dryer. Five different sizes of zirconia balls are added to the ball mill as grinding media, and the mass ratio of zirconia balls of each size is 10 mm diameter zirconia balls: 5 mm diameter zirconia balls: 2 mm diameter zirconia balls: 1 mm diameter zirconia balls: 0.5 mm diameter zirconia balls = 1: (1-2): (1-3): (4-7): (5-10). The material after ball milling has high uniformity, more uniform particle size, and larger specific surface area.
[0039] S3, the slurry obtained in step S2 is mixed and placed in a spray dryer for spray drying, the feed temperature is 160-300°C, the discharge temperature is 60-160°C, the feed rate is 1-5L / h, and the centrifugal disk speed of the spray dryer is 3000-5000rad / min, to obtain a dry raw material powder. During spray drying, zinc oxide and calcium zincate are rapidly generated into calcium zincate crystals, and with the centrifugal atomization of spray drying, the particles are smaller and the specific surface area is larger. The formed calcium zincate crystal particles have high uniformity, and the sulfur-doped carbon coating layer is evenly covered on the surface of the calcium zincate crystals.
[0040] S4, placing the raw material powder obtained in step S3 in a calcining furnace, passing an inert gas under the condition of less than 100 ° C, detecting the oxygen content in the furnace body ≤ 100ppm, and then starting to heat up. The inert gas is a mixed gas composed of one or two of nitrogen and argon. The temperature is raised to a set temperature under the protection of the inert gas, and the temperature is kept and roasted. The roasting temperature is 700-1000 ° C, the heat preservation time is 2-6h, and the sulfur-doped carbon-coated calcium zincate crystals are obtained. During the calcination process, the urea-formaldehyde prepolymer is deeply polymerized and carbonized to obtain a functionalized carbon coating layer. Sulfur doping in the carbon layer will also increase the hydrogen escape overpotential and improve the charge and discharge efficiency.
[0041] The sulfur-doped carbon-coated calcium zincate crystals prepared by the above method have the effect of inhibiting the growth of zinc dendrites, and their solubility in alkaline electrolyte is much lower than that of zinc oxide, thereby effectively improving the performance of zinc-nickel batteries and extending the cycle life of zinc-nickel batteries; sulfur and carbon both have adsorption capacity for zinc elements, which can inhibit the dissolution of meta-zincate ions, thereby reducing the decrease in capacitance during the charging and discharging process of zinc-nickel batteries and improving the battery cycle performance; sulfur-doped carbon can also effectively improve the electrolyte wettability of carbon-coated calcium zincate crystals, improve electrode ion conduction, and help to achieve high-current charging and discharging of zinc-nickel batteries; the doped sulfur will also coordinate with sulfur-philic negative electrode active material elements such as Sn, Sb, and Bi in the electrolyte to form metal coordination polymers, optimize the composition, structure and thickness of the carbon coating layer, thereby improving the specific capacity of the negative electrode material, improving the hydrogen escape potential of the negative electrode material, and further improving the charging and discharging efficiency of the zinc-nickel battery.
[0042] The present invention will be described in detail below through specific embodiments.
[0043] Example 1
[0044] The preparation of sulfur-doped carbon-coated calcium zincate crystals as negative electrode active materials comprises the following steps:
[0045] Add zirconia balls as grinding media into the ball mill. The mass ratio of zirconia balls of various sizes is 10 mm diameter zirconia balls: 5 mm diameter zirconia balls: 2 mm diameter zirconia balls: 1 mm diameter zirconia balls: 0.5 mm diameter zirconia balls = 1:2:2:5:5. Weigh 1 kg of zinc oxide, 0.5 kg of hydrophilic calcium hydroxide and 2 kg of deionized water, add them into the ball mill, set the ball mill speed to 25 rad / min, and the ball milling time to 30 min. After ball milling and mixing, a precursor slurry is formed.
[0046] 0.5 kg of glucose and 0.1 kg of thiourea were added to the precursor slurry, and the ball mill speed was set to 50 rad / min and the ball milling time was 45 min to form a mixed slurry.
[0047] The obtained mixed slurry was placed in a spray dryer for spray drying. The feed rate of the spray dryer was set to 1 L / h, the feed temperature of the spray dryer was set to 240°C, the discharge temperature was set to 160°C, and the centrifugal disk speed of the spray dryer was set to 3000 rad / min. After spray drying, a dry raw material powder was obtained.
[0048] The obtained dry raw material powder is placed in a calcining furnace, heated to 800°C under nitrogen protection, and calcined for 4 hours. After the temperature in the furnace is cooled to room temperature, the material taken out is sulfur-doped carbon-coated calcium zincate crystals.
[0049] The scanning electron microscope image of the sulfur-doped carbon-coated calcium zincate crystal obtained in this example is as follows: Figure 2 and Figure 3 As shown, Figure 4 Compared with the calcium zincate crystals that have not been coated, it can be seen that the surface of the calcium zincate crystals has a uniform coating layer, and the surface becomes rough, and the specific surface area becomes larger. The sulfur-doped carbon coating layer can effectively improve the electrolyte wettability of the calcium zincate crystals, improve the hydroxide ion conduction in the electrode, and help the high current charge and discharge of the zinc-nickel battery. In addition, the formed sulfur-doped carbon coating layer has good conductivity, increases the conductivity of calcium zincate, and makes it easier for calcium zincate to combine with water in the electrolyte to form a stable calcium zincate compound, which not only improves the conductivity of the electrode, but also the formation of calcium zincate is beneficial to reduce the dissolution of the zinc negative electrode and improve the cycle life of the electrode.
[0050] Example 2
[0051] The preparation of sulfur-doped carbon-coated calcium zincate crystals as negative electrode active materials comprises the following steps:
[0052] Add zirconia balls as grinding media into the ball mill. The mass ratio of zirconia balls of various sizes is 10 mm diameter zirconia balls: 5 mm diameter zirconia balls: 2 mm diameter zirconia balls: 1 mm diameter zirconia balls: 0.5 mm diameter zirconia balls = 1:2:2:5:10. Weigh 1 kg of zinc oxide, 0.1 kg of hydrophilic calcium hydroxide and 1.5 kg of deionized water, add them into the ball mill, set the ball mill speed to 30 rad / min, and the ball milling time to 60 min. After ball milling and mixing, a precursor slurry is formed.
[0053] 0.4 kg of fructose and 0.15 kg of thioacetic acid were added to the precursor slurry, and the ball mill speed was set to 20 rad / min and the ball milling time was 30 min to form a mixed slurry.
[0054] The obtained mixed slurry was placed in a spray dryer for spray drying. The feed rate of the spray dryer was set to 1 L / h, the feed temperature of the spray dryer was set to 180°C, the discharge temperature was set to 100°C, and the centrifugal disk speed of the spray dryer was set to 3500 rad / min. After spray drying, a dry raw material powder was obtained.
[0055] The obtained dry raw material powder is placed in a calcining furnace, heated to 1000° C. under argon protection, and calcined for 2 hours. After the temperature in the furnace is cooled to room temperature, the material taken out is sulfur-doped carbon-coated calcium zincate crystals.
[0056] Example 3
[0057] The preparation of sulfur-doped carbon-coated calcium zincate crystals as negative electrode active materials comprises the following steps:
[0058] Add zirconia balls as grinding media into the ball mill. The mass ratio of zirconia balls of various sizes is 10 mm diameter zirconia balls: 5 mm diameter zirconia balls: 2 mm diameter zirconia balls: 1 mm diameter zirconia balls: 0.5 mm diameter zirconia balls = 1:1:3:6:7. Weigh 1 kg of zinc oxide, 0.3 kg of hydrophilic calcium hydroxide and 1 kg of deionized water, add them into the ball mill, set the ball mill speed to 15 rad / min, and the ball milling time to 50 min. After ball milling and mixing, a precursor slurry is formed.
[0059] 0.1 kg of sucrose and 0.2 kg of methionine were added to the precursor slurry, and the ball mill speed was set to 25 rad / min and the ball milling time was 40 min to form a mixed slurry.
[0060] The obtained mixed slurry was placed in a spray dryer for spray drying. The feed rate of the spray dryer was set to 2 L / h, the feed temperature of the spray dryer was set to 300°C, the discharge temperature was set to 150°C, and the centrifugal disk speed of the spray dryer was set to 5000 rad / min. After spray drying, a dry raw material powder was obtained.
[0061] The obtained dry raw material powder is placed in a calcining furnace, heated to 900°C under nitrogen protection, and calcined for 3 hours. After the temperature in the furnace is cooled to room temperature, the material taken out is sulfur-doped carbon-coated calcium zincate crystals.
[0062] Example 4
[0063] The preparation of sulfur-doped carbon-coated calcium zincate crystals as negative electrode active materials comprises the following steps:
[0064] Add zirconia balls as grinding media into the ball mill. The mass ratio of zirconia balls of various sizes is 10 mm diameter zirconia balls: 5 mm diameter zirconia balls: 2 mm diameter zirconia balls: 1 mm diameter zirconia balls: 0.5 mm diameter zirconia balls = 1:1.5:2.5:5:8. Weigh 1 kg of zinc oxide, 0.25 kg of hydrophilic calcium hydroxide and 1.8 kg of deionized water, add them into the ball mill, set the ball mill speed to 5 rad / min, and the ball milling time to 60 min. After ball milling and mixing, a precursor slurry is formed.
[0065] 0.25 kg of starch and 0.25 kg of L-cysteine were added to the precursor slurry, and the ball mill speed was set to 35 rad / min and the ball milling time was 35 min to form a mixed slurry.
[0066] The obtained mixed slurry was placed in a spray dryer for spray drying. The feed rate of the spray dryer was set to 4 L / h, the feed temperature of the spray dryer was set to 200°C, the discharge temperature was set to 90°C, and the centrifugal disk speed of the spray dryer was set to 4000 rad / min. After spray drying, a dry raw material powder was obtained.
[0067] The obtained dry raw material powder is placed in a calcining furnace, heated to 850°C under nitrogen protection, and calcined for 5 hours. After the temperature in the furnace is cooled to room temperature, the material taken out is sulfur-doped carbon-coated calcium zincate crystals.
[0068] Example 5
[0069] The preparation of sulfur-doped carbon-coated calcium zincate crystals as negative electrode active materials comprises the following steps:
[0070] Add zirconia balls as grinding media into the ball mill. The mass ratio of zirconia balls of various sizes is 10 mm diameter zirconia balls: 5 mm diameter zirconia balls: 2 mm diameter zirconia balls: 1 mm diameter zirconia balls: 0.5 mm diameter zirconia balls = 1:2:3:7:8. Weigh 1 kg of zinc oxide, 0.35 kg of hydrophilic calcium hydroxide and 0.8 kg of deionized water, add them into the ball mill, set the ball mill speed to 40 rad / min, and the ball milling time to 40 min. After ball milling and mixing, a precursor slurry is formed.
[0071] 0.4 kg of sucrose and 0.2 kg of L-histidine were added to the precursor slurry, and the ball mill speed was set to 25 rad / min and the ball milling time was 25 min to form a mixed slurry.
[0072] The obtained mixed slurry was placed in a spray dryer for spray drying. The feed rate of the spray dryer was set to 3.5 L / h, the feed temperature of the spray dryer was set to 160°C, the discharge temperature was set to 60°C, and the centrifugal disk speed of the spray dryer was set to 3000 rad / min. After spray drying, a dry raw material powder was obtained.
[0073] The obtained dry raw material powder is placed in a calcining furnace, heated to 720° C. under argon protection, and calcined for 2.5 hours. After the temperature in the furnace is cooled to room temperature, the material taken out is sulfur-doped carbon-coated calcium zincate crystals.
[0074] Example 6
[0075] The preparation of sulfur-doped carbon-coated calcium zincate crystals as negative electrode active materials comprises the following steps:
[0076] Add zirconia balls as grinding media into the ball mill. The mass ratio of zirconia balls of various sizes is 10 mm diameter zirconia balls: 5 mm diameter zirconia balls: 2 mm diameter zirconia balls: 1 mm diameter zirconia balls: 0.5 mm diameter zirconia balls = 1:1:1:6:5. Weigh 1 kg of zinc oxide, 0.15 kg of hydrophilic calcium hydroxide and 1.6 kg of deionized water, add them into the ball mill, set the ball mill speed to 30 rad / min, and the ball milling time to 20 min. After ball milling and mixing, a precursor slurry is formed.
[0077] 0.5 kg of glucose and 0.5 kg of thiourea were added to the precursor slurry, and the ball mill speed was set to 30 rad / min and the ball milling time was 15 min to form a mixed slurry.
[0078] The obtained mixed slurry was placed in a spray dryer for spray drying. The feed rate of the spray dryer was set to 5 L / h, the feed temperature of the spray dryer was set to 220°C, the discharge temperature was set to 110°C, and the centrifugal disk speed of the spray dryer was set to 3300 rad / min. After spray drying, a dry raw material powder was obtained.
[0079] The obtained dry raw material powder is placed in a calcining furnace, heated to 870°C under nitrogen protection, and calcined for 5.5 hours. After the temperature in the furnace is cooled to room temperature, the material taken out is sulfur-doped carbon-coated calcium zincate crystals.
[0080] Comparative Example
[0081] Zinc oxide, calcium zincate crystals and sulfur-doped carbon-coated calcium zincate crystals of Example 1 were used as negative electrode active materials. 600 g of negative electrode active material, 200 g of calcium carbonate additive, 30 g of conductive agent graphite, 100 g of binder 60% PTFE emulsion, and 200 g of dispersant deionized water were weighed, mixed evenly to form a negative electrode slurry, coated on the surface of the current collector to form a negative electrode, and a single cell battery of 1.6 V / 8 Ah was prepared. Battery capacity tests were performed on the three batteries.
[0082] The single-cell battery made of zinc oxide as the negative electrode active material has a rapid attenuation of discharge capacity during the battery capacity test, and its discharge capacity is close to 0 after 50 cycles. The single-cell battery made of calcium zincate crystals without coating treatment as the negative electrode active material begins to decay after more than 150 cycles, and its discharge capacity decays from 8Ah to 6.4Ah after about 360 cycles, and the discharge capacity still remains 80%. The single-cell battery made of sulfur-doped carbon-coated calcium zincate crystals as the negative electrode material begins to decay after more than 700 cycles, and its discharge capacity decays from 8Ah to 6.4Ah after about 720 cycles.
[0083] The above results show that the sulfur-doped carbon-coated calcium zincate crystals of the present invention as negative electrode active materials can effectively inhibit the growth of zinc dendrites and improve the cycle life of zinc-nickel batteries.
[0084] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A negative electrode active material for improving battery cycle life, characterized in that: The negative electrode active material is sulfur-doped carbon-coated calcium zincate crystals, and the raw materials of the sulfur-doped carbon-coated calcium zincate crystals include zinc oxide, hydrophilic calcium hydroxide, a carbon source, a sulfur-containing compound and deionized water.
2. The negative electrode active material for improving battery cycle life according to claim 1, characterized in that: The raw material mass ratio of the sulfur-doped carbon-coated calcium zincate crystals is zinc oxide: hydrophilic calcium hydroxide: carbon source: sulfur-containing compound: deionized water = 1: (0.01-0.5): (0.1-0.5): (0.01-0.5): (0.5-2).
3. The negative electrode active material for improving the battery cycle life according to claim 1 or 2, characterized in that: The carbon source is selected from one or more of the following: glucose, sucrose, fructose and starch; the sulfur-doped carbon-coated calcium zincate crystals; and the sulfur-containing compound material is selected from one or more of the following: thiourea, L-cysteine, thioacetic acid and methionine.
4. The negative electrode active material for improving battery cycle life according to claim 1 or 2, characterized in that: The particle size of the hydrophilic calcium hydroxide is 50-200 nm.
5. A method for preparing a negative electrode active material for improving battery cycle life as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Add grinding media into a ball mill, weigh zinc oxide, hydrophilic calcium hydroxide and deionized water, add them into the ball mill, and mix them by ball milling to form a precursor slurry; S2, weighing a carbon source and a sulfur-containing compound, adding them to the precursor slurry, and continuing ball milling to form a mixed slurry; S3, placing the mixed slurry into a spray dryer for spray drying to obtain a dry raw material powder; S4, placing the raw material powder in a calcining furnace, heating it to a set temperature under the protection of an inert gas, calcining it at the temperature, and cooling it to room temperature to obtain sulfur-doped carbon-coated calcium zincate crystals.
6. The method for preparing a negative electrode active material for improving battery cycle life according to claim 5, characterized in that: In the step S4, the calcination temperature is 700-1000° C. and the holding time is 2-6 hours.
7. The method for preparing a negative electrode active material for improving battery cycle life according to claim 5, characterized in that: The grinding media in step S1 include zirconia balls of five sizes, and the mass ratio of zirconia balls of each size is 10 mm diameter zirconia balls: 5 mm diameter zirconia balls: 2 mm diameter zirconia balls: 1 mm diameter zirconia balls: 0.5 mm diameter zirconia balls = 1: (1-2): (1-3): (4-7): (5-10).
8. The method for preparing a negative electrode active material for improving battery cycle life according to claim 5, characterized in that: The rotation speed of the ball mill in step S1 and step S2 is 5-50 rad / min, and the ball milling time is 15-60 min. In step S3, the feed temperature of the slurry entering the spray dryer is 160-300° C., the discharge temperature is 60-160° C., the feed rate is 1-5 L / h, and the centrifugal disk speed of the spray dryer is 3000-5000 rad / min.
9. A zinc-nickel battery negative electrode material, characterized in that: The invention comprises a negative electrode active material for improving the cycle life of a battery as described in any one of claims 1 to 4.
10. A zinc-nickel battery negative electrode, characterized in that: It comprises a current collector and the negative electrode material as claimed in claim 9, wherein the negative electrode material is coated on the current collector.
Citation Information
Patent Citations
Carbon-coated zinc-base hydrotalcite preparation and application method of carbon-coated zinc-base hydrotalcite in zinc-nickel secondary battery
CN102956875A
Process for preparing calcium zincate as negative electrode material of secondary ZnNi battery
CN1397498A